Respostas
respondido por:
0
Primeiramente:
2x + 3x = 8
5x = 8
x = 8/5
x = 1,6
Após descobrir o valor de x apliquei a equação:
5x = 8
5 . (1,6) = 8 Correto
Depois:
X - Y = -1
X + 1 = Y
1,6 + 1 = Y
Y = 2,6
Então:
X - Y = -1
1,6 - 2,6 = -1
2x + 3x = 8
5x = 8
x = 8/5
x = 1,6
Após descobrir o valor de x apliquei a equação:
5x = 8
5 . (1,6) = 8 Correto
Depois:
X - Y = -1
X + 1 = Y
1,6 + 1 = Y
Y = 2,6
Então:
X - Y = -1
1,6 - 2,6 = -1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás